Phosphorus-containing silicon dioxide aerogel composite material as well as preparation method and application thereof

By using phosphorus-containing silica aerogel composites, the deficiencies in truck fuel tanks in thermal insulation, weather resistance, corrosion resistance and impact resistance are solved, and a fuel tank with excellent performance is prepared to reduce diesel volatility and spontaneous combustion, providing long-term Lifespan and environmentally friendly solutions.

CN119241933APending Publication Date: 2025-01-03HUBEI XINGRUI SILICON MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411327111.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing truck fuel tank cannot have both thermal insulation, weather resistance, corrosion resistance and impact resistance, resulting in large volatility losses of diesel, high antifreeze usage, high probability of diesel spontaneous combustion, and easy to damage in extremely cold temperatures.

Method used

Using phosphorus-containing silica aerogel composite material, by preparing phosphorus-containing silica aerogel powder and polyolefin and other materials to form a truck fuel tank with good flexibility, toughness and impact resistance, using The properties of silica aerogels provide excellent thermal insulation and corrosion resistance.

Benefits of technology

Reduce volatile loss of diesel, reduce the use of antifreeze, reduce the probability of diesel spontaneous combustion, provide a long-life, green and environmentally friendly fuel tank, and has excellent impact resistance, high temperature resistance, low temperature resistance and anti-aging properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a phosphorus-containing silicon dioxide aerogel composite material as well as a preparation method and application thereof, and belongs to the technical field of silicon dioxide aerogel composite materials. The phosphorus-containing silicon dioxide aerogel composite material is prepared from the following components in parts by weight: 40 to 70 parts of phosphorus-containing silicon dioxide aerogel powder, 30 to 40 parts of polyolefin, 5 to 15 parts of dispersing agent and 5 to 15 parts of stabilizer. According to the truck fuel tank prepared from the phosphorus-containing silicon dioxide aerogel composite material, the volatilization loss of diesel oil can be greatly reduced, the use of an anti-freezing agent can be reduced, the spontaneous combustion probability of the diesel oil in the fuel tank can be reduced, and the truck fuel tank prepared from the phosphorus-containing silicon dioxide aerogel has good flexibility and toughness; the high-temperature-resistant and low-temperature-resistant heat-insulating material has the advantages of excellent impact resistance, high temperature resistance, low temperature resistance, excellent heat-insulating property, high corrosion resistance, high aging resistance, long service life and environment friendliness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of silica aerogel composite materials, and in particular to a phosphorus-containing silica aerogel composite material and a preparation method and application thereof. Background Art

[0002] The main purpose of a truck fuel tank is to improve the fuel storage and delivery functions of the truck to ensure long-term operation. In long-distance transportation, the temperature in the north is lower in winter and higher in summer in the south. This temperature difference may affect the properties of the fuel in the tank. The fuel tanks of general trucks are mainly aluminum tanks, iron tanks and plastic tanks.

[0003] The biggest advantage of aluminum fuel tanks over iron fuel tanks is their good corrosion resistance, which is very suitable for high-pressure common rail engines that have high requirements for fuel cleanliness. Secondly, the manufacturing process of aluminum alloy fuel tanks is also relatively simple. It can be made by stamping aluminum plates and then welding them together, which is much simpler than making plastic fuel tanks. The ductility of aluminum alloy material itself is very good. When impacted by external force, even if the aluminum alloy fuel tank is severely deformed, it is not easy to break and leak oil; however, the thermal insulation performance is poor.

[0004] Iron fuel tanks have been used on trucks for a very long time, and have been used since the birth of trucks. Its biggest advantage is that it is cheap. Secondly, the iron fuel tank is strong enough to withstand very strong impacts without being easily damaged, which is very important for trucks that are on the road for a long time and face the threat of accidents at any time. With its high quality and low price, iron fuel tanks have been widely used on various trucks for dozens or even hundreds of years, and many models continue to use iron fuel tanks. But in addition to the above advantages, iron fuel tanks have a more fatal disadvantage, that is, the corrosion resistance is very poor, and it is easy to rust and contaminate the fuel. It is precisely because of this disadvantage that iron fuel tanks have been basically eliminated. Because after the engine entered the era of electronically controlled high-pressure common rail, the fuel system has become more and more sophisticated, and a little impurity in the fuel will cause the expensive injector to be damaged or even scrapped.

[0005] Plastic fuel tanks are also called composite fuel tanks. They are clean and will not pollute the fuel, so they are very suitable for vehicles equipped with electronically controlled engines. Plastic fuel tanks were once installed in large quantities, but after a brief period of glory, they have been basically abandoned. Now only some light trucks continue to use plastic fuel tanks. The reason why plastic fuel tanks have not been widely popularized is still the plastic itself. Although they were once widely used, they cannot adapt to the complex and changeable climatic conditions in my country, such as becoming brittle and fragile in extremely cold temperatures, and cannot be baked with open flames. These problems have limited their application. Currently, only some light trucks are still using them.

[0006] Silica aerogel composite material is a new type of material composed of silica aerogel and other materials. This material has broad application prospects in many fields such as building insulation, industrial insulation, aerospace, etc. By utilizing the characteristics of silica aerogel, a truck tank that meets the performance requirements is prepared, which provides a new research direction to solve the problem that the existing truck tank cannot have both insulation, weather resistance, corrosion resistance and impact resistance. Summary of the invention

[0007] In order to solve the problems of the above-mentioned prior art, the present invention provides a phosphorus-containing silica aerogel composite material and a preparation method and application thereof. The truck fuel tank prepared from the phosphorus-containing silica aerogel composite material provided by the present invention can greatly reduce the loss of diesel volatilization and reduce the use of antifreeze and reduce the probability of spontaneous combustion of diesel in the fuel tank. The phosphorus-containing silica aerogel truck fuel tank has good flexibility and toughness, excellent impact resistance, high temperature and low temperature resistance, excellent thermal insulation performance, strong corrosion resistance and anti-aging performance, long service life, and is green and environmentally friendly.

[0008] The phosphorus-containing silica aerogel composite material comprises the following components in parts by weight: 40-70 parts of phosphorus-containing silica aerogel powder, 30-40 parts of polyolefin, 5-15 parts of dispersant, and 5-15 parts of stabilizer.

[0009] Preferably, the phosphorus-containing silica aerogel powder comprises the following components in parts by weight: 10-20 parts of silicon source, 5-10 parts of phosphorus-based crosslinking agent, 40-50 parts of unsaturated polyester resin, 10-20 parts of water, 30-40 parts of solvent, 5-10 parts of surfactant, and 1-5 parts of catalyst.

[0010] Preferably, the silicon source includes one or more of an organic silicon source or an inorganic silicon source.

[0011] More preferably, the organic silicon source includes one or more of methyl orthosilicate (TMOS), ethyl orthosilicate (TEOS), polyethoxydisiloxane (PEDS), methyltrimethoxysilane (MTMS) or methyltriethoxysilane (MTES).

[0012] More preferably, the inorganic silicon source includes one or more of sodium silicate, rice husk ash, diatomaceous earth or fly ash.

[0013] Preferably, the phosphorus-based crosslinking agent includes one or more of triphenylphosphinocarbonyl acetylacetonate rhodium, phospholipid polyethylene glycol, dialkyl phosphite, diethyl methylphosphonate acrylate, and 2-methacryloyloxyethyl phosphorylcholine.

[0014] Preferably, the surfactant includes one or both of cetyltrimethylammonium bromide and cetyltrimethylammonium chloride.

[0015] Preferably, the catalyst is an acidic catalyst or a basic catalyst.

[0016] Further preferably, the acidic catalyst comprises one or more of hydrochloric acid (HCl), acetic acid (CH3COOH), oxalic acid (HOOCCOOH), hydrofluoric acid (HF) or citric acid.

[0017] More preferably, the alkaline catalyst includes one or more of ammonia water (NH3·xH2O), sodium hydroxide (NaOH) or urea.

[0018] Preferably, the unsaturated polyester resin includes one or more of 191 unsaturated polyester resin, 196 unsaturated polyester resin or 199 unsaturated polyester resin.

[0019] Preferably, the solvent is one or more of methanol, ethanol, isopropanol, n-butanol, etc. and acetone.

[0020] Preferably, the polyolefin includes one or both of polyethylene and polypropylene.

[0021] Preferably, the dispersant includes ZKFS-180 dispersant.

[0022] Preferably, the stabilizer includes one or both of barium alkylphenol and barium laurate.

[0023] The method for preparing the phosphorus-containing silica aerogel composite material comprises the following steps: S1. Preparation of phosphorus-containing silica aerogel powder: S101, mixing and stirring a silicon source, a phosphorus-based crosslinking agent, an unsaturated polyester resin, water, a solvent, a surfactant and a catalyst, and forming a wet gel after a neutralization reaction, a hydrolysis reaction and a condensation polymerization reaction; S102, adding ammonia water to the wet gel in step S101 to adjust the pH value to age the system gel; S103, adding a modifying liquid to convert the hydrophilic groups on the surface of the wet gel into hydrophobic groups; S104, replacing the solvent in the gel network with a solvent having a surface tension lower than that of the solvent in step S101, and then drying the solvent by a normal pressure drying method to obtain a phosphorus-containing silica aerogel powder; S2, adding the phosphorus-containing silica aerogel powder, dispersant and stabilizer prepared in step S1 into the molten polyolefin, and stirring evenly to obtain the product.

[0024] Preferably, the pH value in step S102 is adjusted to 4-6.

[0025] Preferably, the modifying liquid in step S103 includes trimethylchlorosilane.

[0026] Preferably, the amount of the modifying liquid in step S103 is 15% to 60% of the mass of the silicon source.

[0027] Preferably, the solvent having a surface tension lower than that of the solvent in step S101 in step S104 comprises a sodium hydroxide solution or a potassium hydroxide solution.

[0028] More preferably, the concentration of the sodium hydroxide solution or potassium hydroxide solution is 5wt%~10wt%.

[0029] The application of the phosphorus-based silica aerogel composite material in a fuel tank.

[0030] The application comprises the following steps: hot-melting the phosphorus-containing silica aerogel composite material and pouring it into a mold for molding, and then demolding to obtain an oil tank.

[0031] Preferably, the demoulded oil tank is cured for 144 h in an environment with a humidity of 25% and a temperature of 30°C.

[0032] Compared with the prior art, the present invention has the following beneficial effects: 1. The phosphorus-based silica aerogel composite material provided by the present invention has good flexibility and toughness, excellent impact resistance, high temperature and low temperature resistance, excellent thermal insulation performance, strong corrosion resistance and aging resistance, long service life, and is green and environmentally friendly.

[0033] 2. The present invention utilizes the characteristics of silica aerogel to prepare a fuel tank that meets the performance requirements and is applied to trucks, providing a new research direction to solve the problem that the existing truck fuel tanks cannot simultaneously have the characteristics of heat preservation, weather resistance, corrosion resistance and impact resistance. The truck fuel tank prepared from the phosphorus-containing silica aerogel composite material provided by the present invention can greatly reduce the loss of diesel volatilization, reduce the use of antifreeze, and reduce the probability of spontaneous combustion of diesel in the fuel tank. DETAILED DESCRIPTION

[0034] The technical scheme of the present invention is further described below by way of examples. The raw materials used in the examples can be purchased from the market or prepared by conventional methods.

[0035] Example 1 A phosphorus-containing silica aerogel composite material is mainly prepared by the following steps: S1. Preparation of phosphorus-containing silica aerogel powder: S101, taking 12 parts of sodium silicate, 6 parts of triphenylphosphine carbonyl acetylacetonate rhodium, 40 parts of 191 unsaturated polyester resin, 20 parts of water, 30 parts of ethanol, and 5 parts of cetyltrimethylammonium bromide, mixing and stirring them evenly, the sodium silicate undergoes a neutralization reaction under the conditions of an acidic catalyst and H2O as a solvent to generate a large amount of sodium chloride (NaCl), which can be removed by using an ion exchange resin, and then undergoes a hydrolysis and condensation polymerization reaction with triphenylphosphine carbonyl acetylacetonate rhodium, 191 unsaturated polyester resin and cetyltrimethylammonium bromide to form a wet gel; S102, since the pH of the sol system in the previous step is lower than the gel point, ammonia water is added to the wet gel in step S101 to adjust the pH value to 5.2 to age the system gel; S103, adding 4 parts of the modifying liquid trimethylchlorosilane to convert the hydrophilic groups on the surface of the wet gel into hydrophobic groups; S104, using a 10wt% sodium hydroxide solution as solvent to replace the ethanol in the gel network, and then drying it by normal pressure drying to obtain phosphorus-based silica aerogel powder; during the drying process of SiO2 wet gel, the main reason for the shrinkage and collapse of the aerogel is that the capillary force is too large, and the magnitude of the capillary force depends on the surface tension of the solvent in the gel network. Therefore, before the aerogel is dried, it is necessary to replace the high surface tension solvent in the gel network with a low surface tension solvent.

[0036] S2. Add the phosphorus-containing silica aerogel powder prepared in step S1, 7 parts of ZKFS-180 dispersant and 8 parts of stabilizer into 34 parts of polyethylene in a molten state, and stir evenly to obtain the product.

[0037] The application of the phosphorus-containing silica aerogel composite material in a fuel tank comprises the following steps: hot-melting the phosphorus-containing silica aerogel composite material and pouring it into a mold for molding; after demolding, curing it in an environment with a humidity of 25% and a temperature of 30°C for 144 hours to obtain a fuel tank.

[0038] The performance of the fuel tank was evaluated using the GB 18296-2019 standard, and the results are shown in Table 1.

[0039] Table 1 Performance evaluation of fuel tank

[0040] Comparative Example 1 The method is basically the same as Example 1, except that 40-70 parts of ordinary silica aerogel powder, 30-40 parts of polypropylene or polyethylene material, 5-15 parts of dispersant, and 5-15 parts of stabilizer are added to the preparation of the truck fuel tank containing silica aerogel. The phosphorus-containing silica aerogel is added when the polypropylene material is molten, stirred evenly, and then poured into a mold for molding. After demolding, it is cured for 144 hours in an environment with a humidity of 25% and a temperature of 30 ° C to obtain a truck fuel tank containing silica aerogel.

[0041] The performance of the fuel tank was evaluated using the GB 18296-2019 standard, and the results are shown in Table 2.

[0042] Table 2 Performance evaluation of fuel tank

[0043] Comparative Example 2 The method is basically the same as Example 1, except that aerogel is not added in the preparation of the truck fuel tank. 30-40 parts of polypropylene or polyethylene material, 5-15 parts of dispersant, and 5-15 parts of stabilizer are mixed and evenly stirred, then poured into a mold for molding, and after demolding, cured for 144 hours in an environment with a humidity of 25% and a temperature of 30°C to obtain a truck fuel tank.

[0044] The performance of the fuel tank was evaluated using the GB 18296-2019 standard, and the results are shown in Table 3.

[0045] Table 3 Performance evaluation of fuel tank

[0046] It should be understood that the above embodiments are only used to illustrate the present invention and are not used to limit the scope of protection of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the appended claims of the present application.

Claims

1. A phosphorus-containing silica aerogel composite material, characterized in that: The invention comprises the following components in parts by weight: 40-70 parts of phosphorus-containing silica aerogel powder, 30-40 parts of polyolefin, 5-15 parts of dispersant and 5-15 parts of stabilizer.

2. The phosphorus-containing silica aerogel composite material according to claim 1, characterized in that: The phosphorus-containing silica aerogel powder comprises the following components by weight: 10-20 parts of silicon source, 5-10 parts of phosphorus-based crosslinking agent, 40-50 parts of unsaturated polyester resin, 10-20 parts of water, 30-40 parts of solvent, 5-10 parts of surfactant and 1-5 parts of catalyst.

3. The phosphorus-containing silica aerogel composite material according to claim 2, characterized in that: The silicon source includes one or more of an organic silicon source or an inorganic silicon source; the phosphorus-based crosslinking agent includes one or more of triphenylphosphinocarbonyl acetylacetonate rhodium, phospholipid polyethylene glycol, dialkyl phosphite, diethyl methylphosphonate acrylate, and 2-methacryloyloxyethyl phosphorylcholine; the unsaturated polyester resin includes one or more of 191 unsaturated polyester resin, 196 unsaturated polyester resin, or 199 unsaturated polyester resin; the solvent is one or more of methanol, ethanol, isopropanol, n-butanol, etc. and acetone; the surfactant includes one or two of hexadecyltrimethylammonium bromide or hexadecyltrimethylammonium chloride; and the catalyst is an acidic catalyst or an alkaline catalyst.

4. The phosphorus-containing silica aerogel composite material according to claim 3, characterized in that: The organic silicon source includes one or more of methyl orthosilicate, ethyl orthosilicate, polyethoxydisiloxane, methyltrimethoxysilane or methyltriethoxysilane; the inorganic silicon source includes one or more of sodium silicate, rice husk ash, diatomaceous earth or fly ash; the acid catalyst includes one or more of hydrochloric acid, acetic acid, oxalic acid, hydrofluoric acid or citric acid; the alkaline catalyst includes one or more of ammonia water, sodium hydroxide or urea.

5. The phosphorus-containing silica aerogel composite material according to claim 1, characterized in that: The polyolefin includes one or both of polyethylene and polypropylene; the dispersant includes ZKFS-180 type dispersant; and the stabilizer includes one or both of alkylphenol barium and barium laurate.

6. A method for preparing the phosphorus-containing silica aerogel composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Preparation of phosphorus-containing silica aerogel powder: S101, mixing and stirring a silicon source, a phosphorus-based crosslinking agent, an unsaturated polyester resin, water, a solvent, a surfactant and a catalyst, and forming a wet gel after a neutralization reaction, a hydrolysis reaction and a condensation polymerization reaction; S102, adding ammonia water to the wet gel in step S101 to adjust the pH value to age the system gel; S103, adding a modifying liquid to convert the hydrophilic groups on the surface of the wet gel into hydrophobic groups; S104, replacing the solvent in the gel network with a solvent having a surface tension lower than that of the solvent in step S101, and then drying the solvent by a normal pressure drying method to obtain a phosphorus-containing silica aerogel powder; S2, adding the phosphorus-containing silica aerogel powder, dispersant and stabilizer prepared in step S1 into the molten polyolefin, and stirring evenly to obtain the product.

7. The method for preparing the phosphorus-containing silica aerogel composite material according to claim 6, characterized in that: The pH value described in step S102 is adjusted to 4-6; the modifying liquid described in step S103 includes trimethylchlorosilane; the amount of the modifying liquid described in step S103 is 15% to 60% of the mass of the silicon source; the solvent described in step S104 having a surface tension lower than that of the solvent in step S101 includes sodium hydroxide solution or potassium hydroxide solution.

8. The method for preparing the phosphorus-containing silica aerogel composite material according to claim 7, characterized in that: The concentration of the sodium hydroxide solution or potassium hydroxide solution is 5wt%~10wt%.

9. Application of phosphorus-based silica aerogel composite material in fuel tanks, characterized in that: The phosphorus-containing silica aerogel composite material described in any one of 1-5 is hot-melted and poured into a mold for molding, and the fuel tank is obtained after demoulding.

10. The use of the phosphorus-containing silica aerogel composite material in a fuel tank according to claim 9, characterized in that: The demoulded oil tank is cured for 144 h in an environment with a humidity of 25% and a temperature of 30°C.